1993
DOI: 10.1007/bf00336784
|View full text |Cite
|
Sign up to set email alerts
|

Genes for ribosomal proteins S3, L16, L5 and S14 are clustered in the mitochondrial genome of Brassica napus L.

Abstract: We have cloned and sequenced an 8.9-kb mitochondrial-DNA fragment from rapeseed (Brassica napus L.). The nucleotide sequence indicates a gene cluster that encodes four ribosomal proteins (S3, L16, L5, S14), two tRNA genes (trnD, trnK), and the 5' region of the cob gene. The arrangement of these seven genes is trnD-trnK-rps3-rpl16-rpl5-rps14-cob. The rps3 and rpl16 frames overlap by 131 bp. The rpl5 and rps14 genes are separated by a 4-bp spacer. A 1474-basepair intron is located in the rps3 gene. The tRNA(Asp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…1A). Comparison of the amino acid sequences deduced from the cDNAs isolated in this study with the rps14 genes from other plant mitochondria (3,(17)(18)(19) as well as with the rice mitochondrial pseudogene showed 62-73% amino acid identity (Fig. 1B).…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Ismentioning
confidence: 69%
See 2 more Smart Citations
“…1A). Comparison of the amino acid sequences deduced from the cDNAs isolated in this study with the rps14 genes from other plant mitochondria (3,(17)(18)(19) as well as with the rice mitochondrial pseudogene showed 62-73% amino acid identity (Fig. 1B).…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Ismentioning
confidence: 69%
“…The presence of rps14 gene in the mitochondrial genome has been reported from lower plants such as liverwort (3) and chlorophyte alga (16). Among the higher plants, intact rps14 genes have been found in the mitochondrial genome of broadbean (17), Oenothera (18), and rapeseed (19), whereas rps14 is present as a pseudogene in Arabidopsis (20,21) and potato mitochondria (22). The nucleotide and deduced amino acid sequence comparison with those from other plant species showed that the rice rpl5 gene retains an intact ORF, whereas the original reading frame of the rps14 is interrupted by nucleotide deletions at four positions.…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Ismentioning
confidence: 99%
See 1 more Smart Citation
“…B Extension products obtained with L5-18 were coelectrophoresed with sequencing fragments generated with the same primer. A thymidine in the antisense strand (corresponding to an adenine in the sense strand) is detected as 5垄 terminal nucleotide, and lies within a conserved nonanucleotide motif (boxed) Comparison of rpl5 promoter sequences from pea and Oenothera A database analysis of the pea rpl5 upstream region revealed no striking sequence similarity to sequences anking rpl5 genes in other plant species (Brandt et al 1993;Schuster 1993;Ye et al 1993;Quin脛 ones et al 1996). However, inspection of the respective sequences in Oenothera identi庐ed a dierent nonanucleotide motif that is identical to the consensus.…”
Section: Resultsmentioning
confidence: 97%
“…The rpl5-rps14-cob and rrn5-rn18 operons are conserved in most plants (Aubert et al 1992;Ye et al 1993;Quiaeones et al 1996;Hoffmann et al 1999), including squash and watermelon, but are rearranged in Cucumis (Fig. 4B).…”
Section: Mitochondrial Genome Organization Within Cucumismentioning
confidence: 98%